Stone Canvas : towards a better integration of 'rock art' and 'graffiti' studies in Egypt and Sudan - Polkowski, Paweł Lech. (Bibliothèque d'étude,, 2023)
This book presents proceedings of the conference devoted to rock art and graffiti studies in Egypt and Sudan that took place in Cairo from 10th to 12th November, 2019. The thematic spectrum of the contributions is very wide in terms of both their geographical and their chronological range, encompassing figural and textual sources dating from the Late Palaeolithic through the Predynastic, Dynastic, and Graeco-Roman periods, up to Christian and Islamic times. Many of the papers combine evidence from various archaeological domains and also attempt to better integrate graffiti and rock art materials in search of a common ground for research. Thus, the volume provides a good overview of the current state of investigations in these two fields of study in Egypt and Nubia. A book co-published with the Polish Center of Mediterranean Archeology, University of Warsaw.